Analisis Rasio Profitabilitas, Solvabilitas dan Likuiditas Terhadap Harga Saham Perusahaan IDX30 Di Bursa Efek Indonesia - David Kelvincent; Vargo Christian L. Tobing (LPPM Universitas Jambi, 2021)
This research was conducted to determine the effect of profitability, solvency and liquidity ratios on the stock price of IDX30 companies on the Indonesia Stock Exchange. The population in this study were 30 companies listed on the IDX30 index on the Indonesia Stock Exchange. The sampling technique used was purposive sampling and the sample in this study was 15 companies. The data used in this study is secondary data in the form of financial statements. The data is obtained from the Indonesia Stock Exchange website. The results of the t-test showed that the profitability ratio (Net Profit Margin) partially had no significant effect on stock prices, the solvency ratio (Debt Equity to Ratio) partially had no effect on stock prices and the liquidity ratio (Current Ratio) partially had no effect on prices. share. The results of the f test show that profitability (Net Profit Margin), solvency (Debt Equity to Ratio) and liquidity (Current Ratio) simultaneously have no effect on stock prices. In the results of the coefficient of determination, the percentage of the independent variable on the dependent variable is 7.1% and the difference is 92.9% influenced by other factors not examined in this study.